Implementation and Obstacle of Reward and Punishment at Pesantren Al-Azhar-Gresik - Dhuha Hadiyansyah (http://jagadalimussirry.com/, 2022)
This paper is a case study that aims to take a closer look at how punishments and rewards are implemented at the Al-Azhar Islamic Boarding School and what the obstacles are in both male and female dormitories. The data obtained through observation and in-depth interviews. This study found that the Islamic boarding schools have four categories of rules that if violated, the perpetrators will be sanctioned, namely ritual, cleanliness, behavior, and security. The form of punishment is graded ranging from verbal reprimand to being fired from the pesantren or even the formal school. Meanwhile, there are a number of obstacles in the application of rewards and punishment, namely: inconsistency, unilateral rules, lack of knowledge of child psychology, minimal facilities and infrastructure, and imbalance between rewards and punishments